汉语身体动作动词“抓”的词义特征研究 = A study of the lexical meanings of the physical action verb 'Zhua' in Chinese - 林梓婷 Lin, Ziting (2012)
在现代汉语中，有一类词可以被定义为身体动作动词。根据高虹（2001：20）对身体动作动词所给予的定义，作为身体动作动词的第一个标准就是，所描述的动词必须牵涉到身体的某一个部位。这也说明了作为身体动作动词首先要满足的一个条件就是它必须是所指人身体的某个部分发出的动作。在这么多的动作动词当中，以手部动作占大多数。不需持工具用手发出的包括“包”、“放”、“翻”、“捡”等的动作。需要持着工具的手部动作包括“剪”、“刺”、“射”、“抹”等动作。当然，有些手部动作在有工具或无工具的情况下都可以进行，如“打”、“拍”、“敲”等。虽然手部动词占身体动作动词的大多数，但是对这一方面的研究却相当薄弱。除了动词“打”之外，以往的学者对于其他手部动作动词都没有进行深入的研究。 在此，本文就以手部动作动词“抓”为切入口，从不同方面进行探讨。除了作为身体动作动词的释义之外，“抓”还有很多其他的释义，因为它跟许许多多汉语词语一样，是多义性的。而多义词内部的多个义项往往是互相联系，具备引申关系。“抓”字也不例外，除了它的本义之外，它在现代汉语中也已出现了很多不同的义项，其中抽象的用法也包括在内。本文除了探讨“抓”的构词能力与词组搭配之外，也会根据“抓”的词义与义项的匹配情况从语料库中看“抓”各义项的使用频率。除此之外，笔者也会简略地分析“抓”的语义特征与论元角色，探究“抓”用为新词语的现象以及它们在未来的发展概况。最后，本文也会从语义与构词方面对“抓”与其近义词进行分析，看出它们的相似与不同之处。In modern Chinese, there is a class of verbs defined as physical action verbs. These verbs are used to describe the actions performed by human body parts and how we make use of them to perform specific types of actions. Therefore, as long as an action is done by a human body part, it is known as a physical action and thus described by a physical action verb. In the large domain of physical action verbs, hand action verbs make up the majority of them. Hand actions can be performed with or without an instrument. Examples of hand actions without an instrument include “wrap”, “put”, “flip”, “pick”, while hand actions that require an instrument include “cut”, “stab”, “shoot”, “wipe”. There are also certain hand actions that can be done with or without an instrument. These actions are described by the verbs such as “beat”, “tap” and “knock”. Even though hand action verbs make up the majority of physical action verbs, research on them has not been really in-depth. Other than the verb da “hit/beat/strike”, researchers have not really done an in-depth study on other hand action verbs. Therefore, this paper attempts to explore hand action verb zhua “scratch/grasp” from various aspects. Other than having the meanings of a physical action verb, zhua also has many other semantic properties. Just like many other Chinese words, zhua is also a polysemous word. Within a polysemy, its semantic properties and extended meanings are usually related to one another. Zhua is not exceptional. Other than its original meaning, it also has many other meanings in modern Chinese, including metaphorical uses. Other than analysing its ability to form words and phrases, we will look into the usage of zhua in modern Chinese through a thorough search of a modern Chinese language corpus based on the different meanings found from dictionaries.